Sistem Pendukung Keputusan untuk Evaluasi Kinerja Menggunakan Metode TOPSIS: Studi Kasus Penilaian Karyawan - Aditia Yudhistira; Tri Widodo (PT. Tech Cart Press, 2024)
Employee performance evaluation is a systematic process carried out by an organization to assess the contribution, ability, and achievement of individuals in carrying out their duties and responsibilities. This process is not only aimed at identifying the best performers, but also to uncover potential employee development as well as areas for improvement. Employee performance evaluations often face challenges in ensuring the objectivity of the assessment, especially when relying on the subjective perception of the appraiser. Traditional methods often rely on the subjectivity of the assessor, which can result in less accurate or unfair evaluations. In addition, in organizations that have many employees with diverse backgrounds and tasks, consistent and comprehensive assessments are becoming increasingly difficult. The purpose of this study is to implement SPK based on the TOPSIS method to evaluate employee performance objectively and systematically, as well as to increase transparency and consistency in the employee performance evaluation process. The ranking results show the ranking of employee performance evaluation results based on the scores obtained by each candidate. Candidate AF ranked first with the highest score of 0.8471, followed by Candidate SR with a score of 0.7055 got second place. The third position was occupied by HA Candidate with a score of 0.4975. The results of this ranking provide an overview of each candidate's overall performance.